Safety, tolerability, and pharmacokinetics of casimersen in patients with Duchenne muscular dystrophy amenable to exon 45 skipping: A randomized, double‐blind, placebo‐controlled, dose‐titration trial. Issue 3 (29th June 2021) - Wagner, Kathryn R.; Kuntz, Nancy L.; Koenig, Erica; East, Lilly; Upadhyay, Sameer; Han, Baoguang; Shieh, Perry B.
Abstract: Introduction/Aims: Duchenne muscular dystrophy (DMD) is caused by mutations in the DMD gene resulting in the absence of dystrophin. Casimersen is a phosphorodiamidate morpholino oligomer designed to bypass frameshift DMD mutations and produce internally truncated, yet functional, dystrophin protein in patients amenable to exon 45 skipping. Our primary study objective was to evaluate safety and tolerability of casimersen; the secondary objective was to characterize the plasma pharmacokinetics. Methods: This multicenter, phase 1/2 trial enrolled 12 participants (aged 7‐21 years, who had limited ambulation or were nonambulatory) and comprised a 12‐week, double‐blind dose titration, then an open‐label extension for up to 132 weeks. During dose titration, participants were randomized 2:1 to weekly casimersen infusions at escalating doses of 4, 10, 20, and 30 mg/kg (≥2 weeks per dose), or placebo. Results: Participants received casimersen for a mean 139.6 weeks. Treatment‐emergent adverse events (TEAEs) occurred in all casimersen‐ and placebo‐treated participants and were mostly mild (over 91.4%) and unrelated to casimersen or its dose. There were no deaths, dose reductions, abnormalities in laboratory parameters or vital signs, or casimersen‐related serious AEs. Casimersen plasma concentration increased with dose and declined similarly for all dose levels over 24 hours postinfusion. All pharmacokinetic parameters were similar at weeks 7 and 60. Discussion: Casimersen was well tolerated in participants with DMD amenable to exon 45 skipping. Most TEAEs were mild, nonserious, and unrelated to casimersen. Plasma exposure was dose proportional with no suggestion of plasma accumulation. These results support further studies of casimersen in this population.